A Prospective Cohort Study on the Safety of Infant Pentavalent (DTwP-HBV-Hib) and Oral Polio Vaccines in Two South Indian Districts. Issue 5 (May 2020) - Arora, Narendra Kumar; Das, Manoja Kumar; Poluru, Ramesh; Kashyap, Neeraj Kumar; Mathew, Thomas; Mathai, John; Aggarwal, Mahesh Kumar; Haldar, Pradeep; Verstraeten, Thomas; Zuber, Patrick L. F.
Abstract : Background: Safety of pentavalent (DTwP-HBV-Hib) vaccine has been a public concern in India and other countries. This study attempted to document the association of serious adverse events following immunization (AEFI, including hospitalizations and deaths of all causes) with the 3 doses of pentavalent and oral poliovirus (OPV) vaccines. Methods: A cohort of 30, 688 infants in 2 south Indian districts were enrolled and followed-up between October 2014 and May 2016, following their first vaccination with DTwP-HBV-Hib and OPV at public health facilities. During weekly follow-ups, by telephone or home visits, the serious AEFIs (hospitalizations and deaths) occurring any time after each vaccination until 4 weeks after third dose were documented. The incidence risk ratios (IRRs) of serious AEFIs in the first (days 0–6) and fourth weeks (days 21–27) after the vaccine doses were compared using the poisson regression analysis. Results: Of the 30, 688 infants enrolled, 30, 208 received their third doses of vaccines. During the 4-week periods following each vaccination, there were 365 hospitalizations and 17 deaths. Adjusted incidence risk ratio of 3 doses combined for post-vaccination serious AEFIs during the first week compared with fourth week was 0.8 [95% confidence interval: 0.6–1.0]. Conclusions: There was no increased risk of a serious AEFIs during the first week after any of the 3 doses of pentavalent and OPV vaccination compared with the fourth week. In the absence of any temporal clustering, mortality and hospitalization rates observed in vaccinated infants probably reflects the natural occurrence of such events. Abstract : Supplemental Digital Content is available in the text.